Strategi Pembelajaran Pendidikan Agama Islam (PAI) yang Efektif dalam Menumbuhkan Kesadaran Keagamaan - Dewi Safitri; Jessica May Ritonga; Neisya Adhasita (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Learning strategies are crucial because this is the first step given by the teacher. The step that needs to be considered is determining the learning strategy that will accommodate the development of students. The main teacher can choose the best teaching methods and strategies to create excellent learning, adjust the material to the students' abilities, and enable students to receive knowledge transfer. This research uses a descriptive qualitative approach to explore project-based religious learning strategies applied in the Islamic Religious Education subject at SMP Muhammadiyah 05 Medan Denai. This approach was chosen to deeply explore the practices, experiences, and impact of learning on the religious awareness of the students. Interviews with students show that involvement in the project has made them better understand religious values in real life. Some students admitted to starting to pray on time, being more diligent in reading the Quran, and being more concerned about the social environment. This shows that the religious project encourages the internalization of values through direct experience, not just memorization or theory. This learning not only strengthens the understanding of Islamic material but also instills religious values through real practices that can be directly experienced by the students. Some forms of projects, such as mini-dawah, infaq movements, and adab campaigns, have proven to enrich students' experiences and enhance their awareness of Islamic values in daily life. Islamic education teachers play an important role as facilitators, not only guiding students in project activities but also providing space for reflection and evaluation. Students feel more motivated and actively engaged in the learning process, which leads to changes in their religious behavior, such as increased discipline in worship and a greater sense of care for their surroundings.